Generation x - Coupland, Douglas ([S.l.] : Abacus Books, 1996)
Andy, Dag and Claire have been handed a society beyond their means. Twentysomethings, brought up with divorce, Watergate and Three Mile Island, and scarred by the 80s fallout of yuppies, recession, crack and Ronald Reagan, they represent the new generation- Generation X. Fiercely suspicious of being lumped together as an advertiser's target market, they have quit dreary careers and cut themselves adrift in the California desert. Unsure of their futures, they immerse themselves in a regime of heavy drinking and working in no future McJobs in the service industry. Underemployed, overeducated and intensely private and unpredicatable, they have nowhere to direct their anger, no one to assuage their fears, and no culture to replace their anomie. So they tell stories: disturbingly funny tales that reveal their barricaded inner world. A world populated with dead TV shows, 'Elvis moments' and semi-disposible Swedish furniture.